Visualization in Medicine and Life Sciences II Progress and New Challenges - Linsen, Lars.; Hagen, Hans.; Hamann, Bernd; Hege, Hans-Christian.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
For some time, medicine has been an important driver for the development of data processing and visualization techniques. Improved technology offers the capacity to generate larger and more complex data sets related to imaging and simulation. This, in turn, creates the need for more effective visualization tools for medical practitioners to interpret and utilize data in meaningful ways. The first edition of Visualization in Medicine and Life Sciences (VMLS) emerged from a workshop convened to explore the significant data visualization challenges created by emerging technologies in the life sciences. The workshop and the book addressed questions of whether medical data visualization approaches can be devised or improved to meet these challenges, with the promise of ultimately being adopted by medical experts. Visualization in Medicine and Life Sciences II follows the second international VMLS workshop, held in Bremerhaven, Germany, in July 2009. Internationally renowned experts from the visualization and driving application areas came together for this second workshop. The book presents peer-reviewed research and survey papers which document and discuss the progress made, explore new approaches to data visualization, and assess new challenges and research directions. The assembled papers span the frontiers of VMLS, examining these topics: * Feature Extraction * Classification * Volumes and Shapes * Tensor Visualization * Visualizing Genes, Proteins, and Molecules
Part I Feature Extraction -- Part II Classification -- Part III Volumes and Shapes -- Part IV Tensor Visualization -- Part V Visualizing Genes, Proteins, and Molecules.
Keywords: Mathematics; Computer graphics; Computer vision; Biology -- Data processing; Computer science; Visualization; Mathematics; Visualization; Computer Graphics; Computer Appl. in Life Sciences; Mathematical Modeling and Industrial Mathematics; Image Processing and Computer Vision; Computational Science and Engineering